Novel berberine derivatives as adjuvants in the battle against Acinetobacter baumannii: A promising strategy for combating multi-drug resistance - Zhao, Liping; Guo, Xixi; Zhang, Zhimeng; Lu, Xi; Zeng, Qingxuan; Fan, Tianyun; Zhang, Xintong; Chen, Fenbei; Xu, Mengyi; Yuan, Min; Li, Zhenjun; Jiang, Jiandong; et al. (Chinese chemical letters, 2024)
The development of resistance against most of the available antibiotics has made Acinetobacter baumannii (A. baumannii) a pathogen of high risk. In this study, thirty novel berberine derivatives are rationally designed, synthesized, and evaluated for their synergistic antibacterial activities against A. baumannii. Among them, compound 2d shows the most potent synergetic effect to aztreonam against A. baumannii, including carbapenem-resistant and extended-spectrum β-lactamases-producing strains. Moreover, synergistic effects were observed for the combinations of 2d and different antibacterial used in clinical practices, indicating its potent broad-spectrum antibiotic-sensitizing effects against A. baumannii. The combination of 2d and aztreonam significantly improves the survival rates of G. mellonella larvae compared with aztreonam treatment alone. Mechanism studies indicate that 2d inhibits the drug efflux and iron acquisition of the bacteria by targeting the AdeB transporter protein, thus achieving a synergistic antimicrobial efficacy with different antibacterial agents. Therefore, berberine derivatives represent a new family of antimicrobial adjuvants against A. baumannii, with the advantage of dual-function antibacterial effect, and are worthy of further investigation. A new berberine analogue 2d was developed as a synergistic antibacterial candidate against drug-resistant Acinetobacter baumannii through inhibiting the drug efflux and iron acquisition of the bacteria by targeting the Acinetobacter drug efflux B (AdeB) transporter protein. [Display omitted]